A facile fabrication of electrodeposited luminescent MOF thin films for selective and recyclable sensing of nitroaromatic explosives. Issue 14 (9th May 2016) - Zhang, Feng; Wang, Yi; Chu, Tianshu; Wang, Zhongheng; Li, Wei; Yang, Yangyi
Abstract : A one-step fabrication method providing an electrodeposited Eu-TDC MOF thin film as a luminescent sensor for the detection of nitroaromatic explosives with good selectivity and recyclability. Abstract : Rapid detection of nitroaromatic explosives is of utmost importance from the perspectives of civilian safety, the natural environment and human health. Herein, we design a simple yet powerful optical sensing motif based on an electrodeposited luminescent MOF thin film of {[Eu2 (TDC)3 (CH3 OH)2 ]·CH3 OH} (Eu-TDC, where TDC is thiophene-2, 5-dicarboxylate). The parameters of the electrodeposition process were investigated and optimized. The phase and elemental composition of the Eu-TDC film were confirmed using powder X-ray diffraction (PXRD) and energy dispersive spectrometry (EDS), and its morphology and structure were examined using scanning electron microscopy (SEM). This thin film shows extremely good luminescence properties with characteristics of Eu 3+ that are sensitized by the electron-rich ligands, which allows for high efficiency in electron-deficient nitroaromatic explosive sensing. Selective and sensitive responses to a series of nitroaromatic explosives were exhibited, especially for nitrophenols (TNP/DNP/4-NP, K SV > 10 4 M −1 ). It is also an efficient luminescent sensor for detecting nitrobenzene vapour. Significantly, this film can be easily recycled just by washing with methanol. The potential sensing mechanisms are discussed in detail.